Death by dragonfly : a Grace Street mystery - Tesh, Jane (Tesh, Jane. Grace Street mysteries., 2018)
Flamboyant actor Leo Pierson's Art Nouveau treasures have been stolen, including a one-of-a-kind Lalique glass dragonfly he claims is cursed. David Randall, 302 Grace Street's private eye, agrees to recover the valuables before he realizes murder has raised its ugly head in the Parkland art community. Samuel Gallant of the museum board is missing, until Randall and his landlord/consultant Camden find Gallant's body stuffed in a museum closet. When another board member suffers a fatal accident and the art critic for the Parkland Herald is attacked, Randall suspects the stolen dragonfly is indeed cursed. He investigates Richard Mason, curator of the Little Gallery, whose artwork consists of ugly mechanical sculptures, and Nancy Piper, finance manager at the Parkland Art Museum. Meanwhile, Camden struggles against psychic visions he's had since birth, taking pills to limit sudden intense visions. His wife, Ellin, fends off Matt Grabber, a television celebrity healer threatening to take over her Psychic Service Network and using his two large pythons to emphasize his bid. The pythons take a liking to Camden, upping his stress level, while he takes more pills hoping his visions - and the snakes - disappear. Kit, a new tenant at Grace Street, is a young rock star who is also psychic. As Camden becomes more addicted, Kit becomes an early warning system, alerting Randall to the next attack.